Does Total Hip Arthroplasty Influence the Development and Localization of Sacral Insufficiency Fractures?. (19th January 2022) - Graul, Isabel; Strube, Patrick; Vogt, Sophia; Matziolis, Georg; Brodt, Steffen; Hölzl, Alexander
Abstract : Background: Sacral insufficiency fractures (SIFs) are fractures related to reduced bone strength. In a previous study, we noticed that many patients with SIF had undergone total hip arthroplasty (THA). Therefore, the purpose of the present study was to research the localization of clinically apparent SIFs in relation to unilateral THA as well as the influence of unilateral THA on bone mineral density changes in the sacrum. Methods: In this retrospective study, 171 patients with SIFs were screened for unilateral THA. In the group of patients with SIF and THA, the rate of SIF ipsilateral and contralateral to the side of the THA was determined. In a second cohort of 39 THA patients with healthy bone, changes in bone mineral density at the sacral alae ipsilateral and contralateral to the THA were analyzed by use of computed tomography immediately postoperatively and at the 1-year follow-up. Results: Of the 171 patients with SIF, 50 (40 female; mean age, 79 years; range, 54 to 101 years) were previously treated with THA. Of the 50, 31 patients were treated with unilateral THA. The proportion of patients with an SIF contralateral to the THA was 42% (13 of 31) and ipsilateral to the THA was 19% (6 of 31). Twelve patients had bilateral SIFs. The mean age of the THA group without SIF was 62 years (range, 49 to 79 years); 17 were female. The median bone mineral density decreased significantly (p = 0.023), from 35.0 to 13.0 HU, at the sacral ala contralateral to the THA, whereas the decrease of ipsilateral bone mineral density, from 24.0 to 17.0 HU, was not significant (p = 0.361). Conclusions: The proportion of patients with an SIF contralateral to a THA was twice as high as that of patients with an SIF ipsilateral to a THA. These findings are supported by the second cohort's decrease in bone mineral density at the sacral ala contralateral to the THA at 1 year after surgery. We conclude that THA can lead to spatially different remodeling of the sacrum, possibly affecting the development of SIFs. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.